RANGKEP DALAM KARAWITAN JAWA : STUDI KASUS RICIKAN KENDANG - Sigit Setiawan; Supardi Supardi; Sukamso Sukamso (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
This paper is based on the idea that the term deep musical used in Javanese karawitan is also the daily term of the Javanese people. One of them looks at the concept of duplicate. This concept is seen from the point of view of the musicality of the drums. The theory used to reveal the dual concept is the Schutz approach which views humans as